Barangaroo South - Lend Lease Corporation ([Millers Point, New South Wales] : Lend Lease, 2013)
Information publication for the Lend Lease Barangaroo development. Includes artists impressions and sustainability targets.
Keywords: Real estate development -- New South Wales -- Sydney; Housing development -- New South Wales -- Sydney; City planning -- New South Wales -- Sydney; Sustainable buildings -- New South Wales -- Sydney; Architecture -- Environmental aspects -- New South Wales -- Sydney; Australian